Inflammatory pseudotumor of the omentum: An uncommon pediatric tumor - Gupta Chhabi; Mohta Anup; Khurana Nita; Paik Shivani (Wolters Kluwer Medknow Publications, 2009)
Inflammatory pseudotumor is an uncommon tumor with a variable natural course. We report a case of omental pseudotumor in a 6-year-old male child. The child′s clinical presentation was suggestive of an omental mass, which was operated upon after investigations. Histopathology revealed it to be an inflammatory pseudotumor. The case is presented for its unusual location.